Eficiencia del cultivo mora (Rubus glaucus Benth) con la aplicación de nitrógeno y potasio. - Chusin Ayala, Cristian Rene (2024)
Nitrogen (N) is essential for optimal crop development, while potassium (K) plays a crucial role in protein synthesis and in the water and ionic balance of plants. This study seeks to evaluate the efficacy of nitrogen and potassium application in blackberry (Rubus glaucus Benth) crops. Five treatments with four repetitions were implemented by using a randomized block design (RBD) and a statistical analysis was performed by using Tukey's test with a significance level of 5%. Fertilization was carried out in an edaphic manner. Various agronomic variables were examined, such as the number of main and secondary shoots, productive and unproductive branches, flowers, fruit weight and size, as well as yields and associated costs. Treatments T1 (210N + 165 K2O Kg/ha) and T3 (350N + 165 K2O Kg/ha) showed an increase in the number of unproductive branches, with an overall lower performance in the other variables. On the other hand, treatment T2 (210 N + 275 K2O kg/ha) produced a greater number of main and secondary shoots, productive branches and flowers, while treatment T4 (350 N + 275 K2O Kg/ha) generated fruits of greater size and weight. However, yield was significantly higher in the T2 treatment, with 11039.53 kg/ha (equivalent to 11.04 t) with a profitability of 110.28%, representing a favorable economic benefit for farmers